2020
DOI: 10.3390/nu12030688
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an Alkalizing or Acidizing Diet on High-Intensity Exercise Performance under Normoxic and Hypoxic Conditions in Physically Active Adults: A Randomized, Crossover Trial

Abstract: Pre-alkalization caused by dietary supplements such as sodium bicarbonate improves anaerobic exercise performance. However, the influence of a base-forming nutrition on anaerobic performance in hypoxia remains unknown. Herein, we investigated the effects of an alkalizing or acidizing diet on high-intensity performance and associated metabolic parameters in normoxia and hypoxia. In a randomized crossover design, 15 participants (24.5 ± 3.9 years old) performed two trials following four days of either an alkaliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 75 publications
(187 reference statements)
0
6
0
Order By: Relevance
“…They 8 also showed that the alkaline diet improved the buffering capacity in blood and muscle. However, when the same experimental design was applied under hypoxic conditions, it did not improve sprint performance 12 . In the literature, although there is no consensus on the effect of PRAL on exercise performance, it is assumed that vegetarian diets, an example of alkaline nutrition, could improve exercise performance by enhancing antioxidant capacity and the replenishment of glycogen stores, as well as by reducing body weight, body fat, blood pressure, and inflammation 13 .…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…They 8 also showed that the alkaline diet improved the buffering capacity in blood and muscle. However, when the same experimental design was applied under hypoxic conditions, it did not improve sprint performance 12 . In the literature, although there is no consensus on the effect of PRAL on exercise performance, it is assumed that vegetarian diets, an example of alkaline nutrition, could improve exercise performance by enhancing antioxidant capacity and the replenishment of glycogen stores, as well as by reducing body weight, body fat, blood pressure, and inflammation 13 .…”
Section: Introductionmentioning
confidence: 91%
“…Although PRAL studies are mainly focused on kidney patients and diabetic individuals 2 , studies in athletes have also recently begun to be published in the literature 8,9,10,11,12 . A limited number of studies conducted with athletes have focused on the effects of PRAL on aerobic and anaerobic performance as well as on running economy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In one study, fruits and grains but note vegetables and protein were associated with NAE 14 . A recent trial showed that alkaline supplementation improved systemic and tissue acid–base in healthy elderly 15 . During the digestion process, the stomach wall excretes hydrogen ions, the pancreas secretes alkali and the digestive tract absorbs sulfur amino acids 16 .…”
Section: Introductionmentioning
confidence: 99%
“…There are some studies showing that NaHCO 3 can change the content of blood lactate (BLa), HCO 3 − , pH and BE [7][8][9][10] during anaerobic-based exercise. Although those parameters are affected by ingesting NaHCO 3 , the change of anaerobic metabolism systems (AnMS) is different.…”
mentioning
confidence: 99%